The PISA context of statistical graphics in basic education mathematics textbooks in Costa Rica: El contexto PISA de los gráficos estadísticos en los libros de texto de matemáticas de Educación Básica en Costa Rica - Jiménez-Castro, Maynor (2022)
This work aims to analyze the types of statistical graph and associated PISA contexts in mathematics textbooks directed to basic education in Costa Rica. The study includes three complete editorials with a book for each primary education level (7- 11 year old students) and another three editorials for secondary education levels (13-15 year-olds). In total, the distribution of 408 graphs at different levels of education is analyzed and compared with results of previous research. Likewise, the contexts in which the texts are presented are analyzed, using the classification of the PISA studies. There is a good fit of the type of graph, with respect to the curricular orientations and the different contexts are present, with an increasing presence of scientific contexts in secondary education.